(untitled) (Bangladesh Journal of Microbiology, 2011)
The plasmid eliminating abilities of acridine orange, ethidium bromide and sodium dodecyl sulfate were investigated on multi drug resistant Escherichia coli from urinary tract infection specimens. Three different concentrations of each curing agent (Et-Br, SDS and AO) were used. The frequencies of cured cells were 5.55 % (with 50 μg/ml) and 11.76 % (with 75 μg/ml) for acridine orange, 14.29 % (with 100 μg/ml), 21.05 % (with 100 μg/ ml), 17.65 % (with 125 μg/ml) for ethidium bromide and 7.4 % (with 10 % w/v) & 6.67 % (with 10 % w/v) for sodium dodecyl sulfate. However, no cured cells were obtained from 100 μg/ml acridine orange, 75 μg/ml ethidium bromide and 8 and 12 % SDS. Analysis of profiles of wild type and plasmid cured strains by electrophoresis yielded bands of varying sizes for wild type cells, but none were obtained for Et-Br cured cells. Acridine orange treated cells could eliminate only plasmids of 2.7 MDa and another smaller than 2 MDa. Key Words: Plasmid curing; Escherichia coli; Ethidium Bromide; Sodium Dodecyl Sulfate; Acridine Orange. DOI: http://dx.doi.org/10.3329/bjm.v27i1.9165 BJM 2010; 27(1): 28-31